2013
DOI: 10.1007/s11606-013-2381-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors Among Women Veterans at VA Medical Facilities

Abstract: BACKGROUNDHypertension, hyperlipidemia, diabetes, and obesity in middle adulthood each elevate the long-term risk of cardiovascular disease (CVD). The prevalence of these conditions among women veterans is incompletely described.OBJECTIVETo describe the prevalence of CVD risk factors among women veterans in middle adulthood.DESIGNSerial cross-sectional studies of data from the Diabetes Epidemiologic Cohorts (DEpiC), a national, longitudinal data set including information on all patients in the Veterans Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Together hypertension and hyperlipidemia form the most common latent class, “At Risk of CVD” (37.5%). This result is consistent with the findings of Vimalananda et al (2013) who found that rates of CVD disease are shown to increase as women Veterans age (~25% of women aged 45–54 and ~33% of women aged 55–64 in VHA have more than two CVD risk factors).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Together hypertension and hyperlipidemia form the most common latent class, “At Risk of CVD” (37.5%). This result is consistent with the findings of Vimalananda et al (2013) who found that rates of CVD disease are shown to increase as women Veterans age (~25% of women aged 45–54 and ~33% of women aged 55–64 in VHA have more than two CVD risk factors).…”
Section: Discussionsupporting
confidence: 92%
“…The most common condition for our cohort was hypertension, with 63.4% of all senior-aged women Veterans having a diagnosis in their records; this finding is consistent with the 2013 study of cardiovascular health in women Veterans ( Whitehead, 2013 ). This percentage represents a substantial increase in the rate of hypertension for women Veterans as they age, as Vimalananda et al (2013) found hypertension in 13% of women Veterans aged 35–44, 28% of women Veterans aged 45–54, and 42% of women Veterans aged 55–64. On the other hand, this rate is lower than in the general population of senior-aged women in the United States, where 70.8% women ages 65–74 and 80.1% of those over 75 years of age have hypertension ( Centers for Disease Control and Prevention, 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, women had similar prevalence of risk factors for heart disease (i.e., hypertension, high cholesterol) when comparing men and women within the same age strata (45-64 and !65 years). The prevalence of hypertension and high cholesterol among women veterans was strikingly high (>44% in women ages 45-64 years and >60% in women ages !65 years), consistent with previous studies (Vimalananda et al, 2013). Given the predominance of hypertension and diabetes observed in women veterans, it is remarkable that the Danan et al (2017) review of women veterans' health did not identify any published clinical research studies with a primary focus on hypertension and only three studies on diabetes that included women veterans.…”
Section: Discussionsupporting
confidence: 83%
“…5 An important finding by gender showed that women had 8% higher odds of 3+ comorbidities and 16% higher odds of both medical and mental health comorbidities than men. Studies have also shown greater CVD risk burden 29 and mental health disorders in women, 30 who represent a growing population of veterans. The significantly lower multimorbidity among married veterans resonates with other studies showing this finding as an important support mechanism for male versus female veterans.…”
Section: Discussionmentioning
confidence: 99%